2008
DOI: 10.1021/la800632r
|View full text |Cite
|
Sign up to set email alerts
|

On the Origins of Sudden Adhesion Loss at a Critical Relative Humidity: Examination of Bulk and Interfacial Contributions

Abstract: The origins for abrupt adhesion loss at a critical relative humidity (RH) for polymeric adhesives bonded to inorganic surfaces have been explored using a model poly(methyl methacrylate) (PMMA) film on glass. The interfacial and bulk water concentrations within the polymer film as a function of D 2O partial pressure were quantified using neutron reflectivity. Adhesion strength of these PMMA/SiO 2 interfaces under the same conditions was quantified using a shaft loaded blister test. A drop in adhesion strength w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…These measurements of the interfacial structure provide a mechanism to better understand the underlying mechanisms by which interfaces are attacked by environmental factors. We have previously used the combination of NR and fracture mechanics to elucidate a probable mechanism for humidity‐induced failure: this is swelling stress driven that is induced by reorganization of adsorbed water at the polymer adhesive‐inorganic interface . This explanation, aided by NR measurements to elucidate the distribution of water within the adhesives, is consistent with many of the prior explanations that independently may appear to be contradictory as some have proposed the bulk swelling to be important for humidity failure , while others have solely focused on the interface .…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…These measurements of the interfacial structure provide a mechanism to better understand the underlying mechanisms by which interfaces are attacked by environmental factors. We have previously used the combination of NR and fracture mechanics to elucidate a probable mechanism for humidity‐induced failure: this is swelling stress driven that is induced by reorganization of adsorbed water at the polymer adhesive‐inorganic interface . This explanation, aided by NR measurements to elucidate the distribution of water within the adhesives, is consistent with many of the prior explanations that independently may appear to be contradictory as some have proposed the bulk swelling to be important for humidity failure , while others have solely focused on the interface .…”
Section: Introductionsupporting
confidence: 56%
“…The width of the epoxy‐aluminum oxide interface is very similar for the dry and salt cases, but immersion in D 2 O leads to a significant broadening of this interface, which has been attributed to water accumulation . Additionally prior studies on the role of humidity on adhesion illustrated a decrease in adhesion as the width of this interface increases . However, the ambiguity associated with two possible absorbing species (D 2 O and NaCl) does not allow for the concentration profiles to be elucidated from these experiments without additional information.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, Lefebvre et al [136] found that a completely different mechanism, which only involves the bulk adhesive properties, was responsible for the sudden loss of adhesion in an epoxy/glass system. Inspired by the importance of critical moisture content and contradictory literature regarding its underlying mechanisms, Tan et al [137][138][139] used detailed characterisation methods and proposed a combined bulk-interfacial mechanism for the loss of adhesion at or above the critical moisture content. As illustrated in Figure 8, the interface moisture content increases as the surrounding humidity level increases and this in turn reduces the contact area between adhesive and substrate.…”
Section: Effect Of Moisture On Adhesively Bonded Jointsmentioning
confidence: 99%
“…While most synthetic adhesive systems are negatively affected by increased humidity10, viscid-silk glue generates higher adhesion forces as humidity increases, and in some species adhesion continues to improve at conditions close to 100% relative humidity (R.H.)8. Therefore, understanding the glue composition and its adhesion mechanism can provide a framework to design synthetic adhesives that function in humid environments.…”
mentioning
confidence: 99%